Ancient Babylonian Grammatical Theory - Black, J. A.
Diss. D. Phil.; 1. Verbal Paradigms; 2. Grammatical Vocabularies, Analyses, Epitomes and Related Texts; 3. Grammatical Terms; 4. Conclusions; 5. Appendices. Texts utilized include MSL IV, paradigms from Ur (UET VII 97-1C2), Examentext A, K.4808 and duplicates.